Characterizing the maximum number of layers in chemically exfoliated graphene - Szirmai, Péter; Márkus, Bence G.; Chacón-Torres, Julio C.; Eckerlein, Philipp; Edelthalhammer, Konstantin; Englert, Jan; Mundloch, Udo; Hirsch, Andreas; Hauke, Frank; Náfrádi, Bálint; Forró, László; Kramberger, Christian; et al. (Scientific Reports, 2019)
An efficient route to synthesize macroscopic amounts of graphene is highly desired and bulk characterization of such samples, in terms of the number of layers, is equally important. We present a Raman spectroscopy-based method to determine the typical upper limit of the number of graphene layers in chemically exfoliated graphene. We utilize a controlled vapour-phase potassium intercalation technique and identify a lightly doped stage, where the Raman modes of undoped and doped few-layer graphene flakes coexist. The spectra can be unambiguously distinguished from alkali doped graphite, and modeling with the typical upper limit of the layers yields an upper limit of flake thickness of five layers with a significant single-layer graphene content. Complementary statistical AFM measurements on individual few-layer graphene flakes find a consistent distribution of the layer numbers.
CRIS-Team Scopus Importer:2019-12-31